Edukasi Kesehatan Digital: Strategi Menjaga Keseimbangan Antara Penggunaan Gadget dan Kesehatan Siswa di SMA Negeri 2 Medan: Digital Health Education: Strategies for Maintaining Balance Between Gadget Use and Student Health at SMA Negeri 2 Medan - Sihotang, Supran Hidayat; Sari, Nurmala; Razali, Mariany; Sembiring, Fanny Rizki; Nadia, Syarifah; Ginting, Ernawaty; Silvany, Rika; Siregar, Wilda Wahyuni; Ramadhan, Raihan Zaki (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The development of digital technology has made gadget use an integral part of adolescent life, including high school students. Excessive use, especially during Ramadan, can disrupt students' biological rhythms, sleep quality, and mental health. This community service activity aims to improve students' digital health literacy through an educational seminar themed "Maintaining Balance Between Health and Gadget Use During Ramadan" held at SMA Negeri 2 Medan. The method used was participatory education through the delivery of interactive materials and evaluation using pre-test and post-test questionnaires. Quantitative results showed a 40.4% increase in students' understanding scores, with 76% of participants increasing by more than 20 points. Meanwhile, qualitative results showed increased student awareness of the negative impacts of gadgets and a growing commitment to manage their use more healthily. This activity successfully integrated e-health literacy, Ramadan values, and time management strategies as a contextual educational approach. These findings support the importance of school-based digital health education in shaping healthy lifestyle behaviors and wise technology use among adolescents. This program is recommended as a promotive-preventive intervention model that can be implemented sustainably through collaboration between schools, teachers, and families.